Ambiguitas Status Hukum Santri sebagai Relawan dalam Pekerjaan Konstruksi Pesantren: Perspektif Perlindungan Anak dan Hukum Ketenagakerjaan - Fajar Pradita; Ahmad Heru Romadhon; Dhofirul Yahya (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
The involvement of students (santri) in the construction of Islamic boarding schools (pesantren) is often positioned as voluntary or religious service activities. However, in practice, such involvement frequently contains elements of command, task allocation, and occupational risk that resemble an employment relationship. This condition creates ambiguity regarding the legal status of santri and potentially leads to a lack of legal protection, particularly when workplace accidents occur during construction activities. This study aims to analyze the legal status of santri involved in pesantren construction and the implications for legal responsibility related to occupational safety and child protection. This research employs a normative juridical method using statutory and conceptual approaches through the analysis of primary, secondary, and tertiary legal materials. The results indicate that the involvement of santri in construction activities that involve elements of instruction, supervision, and division of labor may indicate the existence of an employment relationship under labor law, thereby creating legal obligations regarding occupational safety and potential liability for pesantren management. This study provides a legal analytical framework for defining the boundary between religious volunteer activities and employment relationships that carry legal responsibilities for pesantren, particularly in the context of child protection and occupational safety in construction activities.